Gamma Ray Signatures of Neutrons From a Terrestrial Gamma Ray Flash. Issue 19 (13th October 2017) - Bowers, G. S.; Smith, D. M.; Martinez‐McKinney, G. F.; Kamogawa, M.; Cummer, S. A.; Dwyer, J. R.; Wang, D.; Stock, M.; Kawasaki, Z.
Abstract: Following a lightning strike to a wind turbine in Japan, we have observed a large burst of neutrons lasting 100 ms with a ground fluence of 1, 000 n cm −2, thousands of times greater than the peak neutron flux associated with the largest ground level solar particle event ever observed. This is the first detection of an unequivocal signature of neutrons from a terrestrial gamma ray flash, consisting of a 2.223 MeV gamma‐ray spectral line from a neutron‐capture on hydrogen reaction occurring in our detector, and is shown to be consistent with the production of 10 12 –10 13 photoneutrons from a downward terrestrial gamma ray flash (TGF) at 1.0 km, with a gamma ray brightness typical of upward TGFs observed by satellites. Key Points: Gamma rays producing a neutron flash with a ground fluence of 1, 000 n cm −2 and 100 ms duration was observed following a lightning strike This observation is consistent with simulations of photoneutron production from a terrestrial gamma ray flash (TGF) with typical brightness These measurements definitively show that low altitude atmospheric electricity can drive nuclear processes Plain Language Summary: Using detectors to measure gamma‐rays, we have observed a cloud of neutrons following a lightning strike to a wind turbine in Japan.